Analisis Gaya Kepemimpinan dalam Keterikatan Karyawan di PT. DMI: Studi Kasus Kualitatif - Djaluputro, Supartopo; Andrias, Mone Stepanus (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The research explores the impact of differences in the interpretation of leadership values on leadership styles and employee engagement within a department. The analysis was conducted based on interviews with eleven respondents. The research approach used is qualitative case studies. Research findings reveal different interpretations of leadership values can lead to negative leadership styles and decreased employee engagement. The research also highlights that proper implementation of leadership values can result in a positive leadership style and increased employee engagement. In addition, the study shows a strong link between the implementation of leadership values and employee engagement. Overall, the study emphasizes the importance of understanding and correctly interpreting leadership values in determining leadership styles and employee engagement.